The location of phosphorylation sites and Ca2+-dependent proteolytic cleavage sites on the major neurofilament polypeptides from Myxicola infundibulum. - Eagles, P A (1981)
1. When axoplasm is incubated with [32P]Pi the main phosphorylated components are the neurofilament polypeptides. 2. Activation with Ca2+ of the proteinase present in axoplasm causes degradation of these neurofilaments and the peptides produced by this reaction have been analysed by fingerprinting. 3. Fingerprinting shows that initially the Ca2+-activated proteinase cleaves the neurofilament polypeptides at three major sites producing polypeptides with mol.wts. 70,000, 50,000 and 47,000. 4. These polypeptides sediment with filaments, originate from the tail-region of the molecule and contain a little radioactive label. 5. As these polypeptides are produced, other polypeptides that come from the head-region of the molecule are liberated as soluble products that contain the bulk of the radioactivity. 6. Fingerprinting therefore shows that at least two regions on the molecule are phosphorylated and that the major one is located towards the head-end of the polypeptides.